Activated γδ T cells exhibit cytotoxicity and the capacity for viral clearance in patients with acute hepatitis B - Jia, Zheng-Hu (Clinical immunology (Orlando, Fla.), 2019)
Copyright © 2019 Elsevier Inc. All rights reserved.